Indigenous people's innovation : intellectual property pathways to development - Drahos, Peter, 1955-; Frankel, Susy (Open Access e-Books, 2012)
Traditional knowledge systems are also innovation systems. This book analyses the relationship between intellectual property and indigenous innovation. The contributors come from different disciplinary backgrounds including law, ethnobotany and science.